Hydrology of Small Forested Catchments in the Arid Region of Rajasthan - Khan, M A; Tewari, J C; Issac, V C (Annals of Arid Zone, 2016)
Hydrology of small catchments dominated by Acacia tortilis and Colophospernnun mopane forested catchments was studied during the 1993 and 1994 monsoon seasons. Nearly % of throughfall was received from plots moved with A. tortilis compared with 79.9% in C. moporre plots. Canopy inrcrception averaged 21.4% for C. mopane forest stand and 13.1% lor the A. tortilisÂ forest stand. Interception was positively related with canopy mver and negatively related with throughfall. Stemflow was influenced by lree species characteristics. Plot size had no cmrt an ranow interrcption, thmughfall and stemflow. Surface runoff in plots with A. tonilk mver was neariy 53% highcr wmparrd with C. mopme stand. Among plots higher surface runoff was received from 10 m x 10 m plots.